MEDIA CLOUD STORAGE PADA POSYANDU ASOKA II JATI RANGGON BEKASI - Rizki Ridwan; Nunu Kustian; Siti Julaeha (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Cloud-based storage as an online-based alternative by using an internet connection in accessing data, but its application is still minimally used by community empowerment forums, one of which is Posyandu Asoka II Jatiranggon Bekasi which still stores activity data into cadre smartphones so that data loss and damage often occur. even cause human error in reporting Posyandu activities every month. The method used is lectures and participatory action studies as a form of action to find out the real obstacles experienced by the use of technology by posyandu cadres in social life by carrying out the planning stage, the implementation stage of implementing cloud storage, namely Microsoft OneDrive, and the evaluation stage of the extent to which cadres use data storage technology into cloud computing as a solution for posyandu cadres to make new breakthroughs with large, free, and environmentally friendly capacities and minimize unwanted events.